2011
DOI: 10.7857/jsge.2011.16.6.143
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Characteristics of Uranium and Radon Concentration in Groundwaters of Provinces in Korea

Abstract: In order to figure out the characteristics of radionuclides concentrations of nine provinces, we analyzed uranium and radon in 681 samples of groundwater. Most of uranium concentrations in each province were less than 10 µg/L, and Gyeongnam, Jeonnam, Jeju provinces did not have groundwaters exceeding the US EPA drinking water MCL (30µg/L) of uranium. The ratio of radon values exceeding US EPA drinking water AMCL (4,000 pCi/L) was 22.6% (154/681) and Gyeongnam and Jeju provinces had no groundwaters exceeding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Agricultural greenhouses carry a greater risk of radon exposure than typical buildings because of the abundance of exposed soil, and farmers working in the early morning are exposed to radon that accumulates nightly in sealed greenhouses [ 8 , 9 ]. Water curtain cultivation (WCC) facilities spray groundwater to form a water film on the inner houses for heat insulation in the winter season, which leads to an additional risk of radon in the groundwater being released into the air [ 10 , 11 ]. A case study showed that radon concentrations in three nearby WCC facilities reached a few thousand Bq/m 3 and varied greatly among the measuring sites [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural greenhouses carry a greater risk of radon exposure than typical buildings because of the abundance of exposed soil, and farmers working in the early morning are exposed to radon that accumulates nightly in sealed greenhouses [ 8 , 9 ]. Water curtain cultivation (WCC) facilities spray groundwater to form a water film on the inner houses for heat insulation in the winter season, which leads to an additional risk of radon in the groundwater being released into the air [ 10 , 11 ]. A case study showed that radon concentrations in three nearby WCC facilities reached a few thousand Bq/m 3 and varied greatly among the measuring sites [ 12 ].…”
Section: Introductionmentioning
confidence: 99%